Comparative evaluation of axillary and rectal temperatures across different gestational ages in newborns admitted to the neonatal intensive care unit: a cross-sectional study - Shaimaa Halabi; Rana Almuqati; Amenah Al Essa; Manal Althubaiti; Musab Alshareef; Abdulaziz Homedi; Ahmed Alwatban; Mohanned Alrahili; Saif Alsaif; Kamal Ali (BMC, 2024)
Abstract Objective Maintaining normothermia is crucial for neonatal survival, especially in preterm infants prone to temperature instability. This study evaluates the correlation and variability between axillary and rectal temperatures at Neonatal Intensive Care (NICU) admission across gestational age ranges of 23-28, 29-32, 33-36, and ≥ 37 weeks, aiming to inform improved neonatal thermal management strategies. Methods This cross-sectional study was conducted at King Abdulaziz Medical City, Riyadh, from October 2023 to April 2024, involving 160 infants. Admission temperatures were measured using digital thermometers. Data analysis included ANOVA/Kruskal-Wallis for continuous variables, Chi-square tests for categorical data, Bland-Altman method for agreement assessment, and Pearson correlation coefficients to evaluate temperature correlations. Results Mean axillary temperature increased from 36.4 °C in the 23-28 weeks gestational group, to 36.5 °C in the 29-32 weeks group, and to 36.7 °C in the 33-36 weeks and ≥ 37 weeks groups, (p = 0.033). Rectal temperature increased from 36.5 °C in the 23-28 weeks group, to 36.6 °C in the 29-32 weeks group, and reached 36.8 °C in both the 33-36 weeks and ≥ 37 weeks groups (p = 0.006). Notable differences between measurement methods were observed in the 33-36 and ≥ 37 weeks groups (p < 0.001), with less pronounced differences in the 23-28 and 29-32 weeks groups. While temperature differences between rectal and axillary measurements remained consistent across all groups at 0.1 °C (p = 0.779), neonatal outcomes varied significantly across gestational age groups, with younger infants exhibiting lower survival rates (p < 0.001), higher incidences of hypoglycemia (p < 0.001) and sepsis (p < 0.001), and extended durations of ventilation (p < 0.001) and hospital stay (p < 0.001). Strong correlations between rectal and axillary temperature were found across all age ranges (Pearson coefficients: 0.953 for 23-28 weeks, 0.762 for 29-32 weeks, 0.910 for 33-36 weeks, and 0.761 for ≥ 37 weeks; all p < 0.001). Bland-Altman analysis indicated higher variability in agreement for younger preterm groups, showing limits of agreement ranging from − 0.5 to 0.65 °C for 23-28 weeks and − 0.5 to 0.69 °C for 29-32 weeks, improving in older groups with − 0.2 to 0.4 °C for 33-36 weeks and similarly narrow ranges for ≥ 37 weeks. Conclusion Both rectal and axillary temperatures showed variation across different age groups, exhibiting a substantial overall correlation. Notable differences between the two methods were observed in the 33-36 weeks and ≥ 37 weeks groups. Younger preterm infants demonstrated greater variability, with enhanced agreement observed in older infants.